การใช้ถ่านกระดูกกำจัดคลอรีนแมงกานีสและสีจากน้ำ - สุดาวดี อุตชี (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
This research is a feasibility study in using bone charcoal for chlorine manganese, and color removal from water. Physical characteristics of bone charcoal have been examined, batch adsorption studies have been conducted to determine the effects of contact time, dose of absorbent, concentration and pH and the experiment for adsorption capacity have been performed. The results indicated that time, solution pH, initial concentration, and bone charcoal weight affected the adsorption capacity. The appropriate conditions for chlorine removal were using bone charcoal weight of 0.5 grams at pH 6-7 for 70 minutes, manganese removal were using bone weight of 1 gram at pH 5-7 for 7 hours, and color Removal were using bone weight of 1 gram at pH 6-7 for 3 days. For adsorption column experiment, 1 centimeter diameter and 10 centimeters depth column were used the efficiency of chlorine removal by the column was 98.95% when tap- water was feed through. For manganese removal from surface water the column can remove manganese to less than 0.3 ppm for 1101 BV.